Cross-cultural adaptation of the oral health impact Profile (OHIP) for the Malaysian adult population - Saub, R.; Locker, D.; Allison, P.; Disman, M. (2007)
Objective: The aim of this project was to develop an oral health related-quality of life measure for the Malaysian adult population aged 18 and above by the cross-cultural adaption the Oral Health Impact Profile (OHIP). Method: The adaptation of the OHIP was based on the framework proposed by Herdman et al (1998). The OHIP was translated into the Malay language using a forward-backward translation technique. Thirty-six patients were interviewed to assess the conceptual equivalence and relevancy of each item. Based on the translation process and interview results a Malaysian version of the OHIP questionnaire was produced that contained 45 items. It was designated as the OHIP(M). This questionnaire was pre-tested on 20 patients to assess its face validity. A short 14-item version of the questionnaire was completed by 171 patients to assess the suitability of the Likert-type response format. Field-testing was conducted in order to assess the suitability of two modes of administration (mail and interview) and to establish the psychometric properties of the adapted measure. Results: The pre-testing revealed that the OHIP(M) has good face validity. It was found that the five-point frequency Likert scale could be used for the Malaysian population. The OHIP(M) was reliable, where the scale Cronbach's alpha was 0.95 and the ICC value for test-retest reliability was 0.79. Three out four construct validity hypotheses tested were confirmed. OHIP(M) works equally well as the English version. Conclusion: OHIP(M) was found to be reliable and valid regardless of the mode of administration. However, this study only provides initial evidence for the reliability and validity of the measure. Further study is recommended to collect more evidence to support these results.